Comparison of Serum Vitamin D Status Between Tuberculous Lymphadenitis Patients and Healthy Controls (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Extra pulmonary tuberculosis accounts for 20% of all tuberculosis cases, among them 35% are tuberculous lymphadenitis. Persistent and/or paradoxically enlarged lymph node, newly developed lymph node as well as suppuration of the lymph node give rise to controversies about duration of therapy, mode of treatment and further evaluation. Various outcomes not only affect the patients psycho-socially and economically but also burdened the country’s Tuberculosis Control Program me. So it is wise to search the possible links to prevent these situations. Vitamin D has a significant role in stimulating macrophage and the subsequent limitation of Mycobacterium tuberculosis growth as well as acceleration of resolution of inflammatory responses secondary to it which is mainly responsible for these various outcomes. The present study was attempted to determine the status of serum vitamin D concentration in patient with tuberculous lymphadenitis and to compare it with apparently healthy controls.Materials and methods: This case-control study was conducted in the Department of Internal Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU) between May 2016 and March 2017.Thirtyone (31) newly diagnosed patients of tuberculous lymphadenitis were selected as cases and equal numbers of age-sex matched apparently healthy individuals were taken as controls for the study. Different diagnostic modalities (FNAC, Histopathology and PCR) were employed to diagnose the cases. Blood samples were collected and estimated for serum vitamin D [25(OH) D] by Chemiluminescent Immunoassay (CLIA) method. Serum vitamin D